2012
DOI: 10.1159/000336027
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis to Peanut in a Patient Predominantly Sensitized to Ara h 6

Abstract: Diagnosis of peanut allergy has improved thanks to component-resolved diagnostics. Peanut allergen component Ara h 2 is considered to indicate true peanut allergy. The component Ara h 6 is structurally similar to Ara h 2, but the diagnostic value of analyzing IgE antibodies to Ara h 6 is unclear. A boy sensitized (≥0.35 kUA/l) to Ara h 8 but not to Ara h 1, Ara h 2 and Ara h 3 was challenged with peanut and developed grade II anaphylaxis. In serum collected at the time of challenge a doubling of IgE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
1
29
1
Order By: Relevance
“…Some other clinically relevant peanut allergen component, such as Ara h 6, may exist in our population. Asarnoj et al [25] had reported a case of anaphylaxis to peanuts in a patient with a high level of anti-Ara h 6 IgE but a low level of anti- Ara h 2 IgE. Further studies should take this allergen into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Some other clinically relevant peanut allergen component, such as Ara h 6, may exist in our population. Asarnoj et al [25] had reported a case of anaphylaxis to peanuts in a patient with a high level of anti-Ara h 6 IgE but a low level of anti- Ara h 2 IgE. Further studies should take this allergen into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…30 He did not follow the study protocol because he was participating in a pilot investigation for this study. After the final dose of 10 g of peanut at challenge, he experienced grade II anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…All of these sensitizations have been shown to cause allergic reactions [32, 43, 45]. Ara h 6 monosensitization has been found on rare occasions in other studies, but in our study 2 individuals out of 6 peanut allergic and Ara h 2-negative individuals were monosensitized to Ara h 6, which could indicate that Ara h 6 monosensitization is common in the Icelandic peanut allergic population [30]. In contrast to what has been shown in Spain, sensitization to Ara h 9 was not shown to be clinically important in Iceland, although the cases may be too few to generalize [46].…”
Section: Discussionmentioning
confidence: 42%
“…Ara h 2 and Ara h 6 are both 2S albumins and have 59% amino acid homology, which causes Ara h 6 to cross-react extensively with Ara h 2 [29]. In rare cases, individuals can be sensitized to Ara h 6 without being sensitized to Ara h 2 [30, 31]. Ara h 8 is a homologue of the major birch pollen allergen Bet v 1 and it is rarely associated with severe allergic reactions.…”
Section: Introductionmentioning
confidence: 99%